Participation of the Serine Protease Jonah66Ci in the Drosophila Antinematode Immune Response. - Yadav, S.; Eleftherianos, I. (Infection and Immunity, 2019)
Serine proteases and serine protease homologs form the second largest gene family in the Drosophila melanogaster genome. Certain genes in the Jonah multigene family encoding serine proteases have been implicated in the fly antiviral immune response. Here, we report the involvement of Jonah66Ci in the Drosophila immune defense against Steinernema carpocapsae nematode infection. We find that Drosophila Jonah66Ci is upregulated in response to symbiotic (carrying the mutualistic bacterium Xenorhabdus nematophila) or axenic (lacking Xenorhabdus) Steinernema nematodes and is expressed exclusively in the gut of Drosophila larvae. Inactivation of Jonah66Ci provides a survival advantage to larvae against axenic nematodes and results in differential expression of Toll and Imd pathway effector genes, specifically in the gut. Also, inactivation of Jonah66Ci increases the numbers of enteroendocrine and mitotic cells in the gut of uninfected larvae, and infection with Steinernema nematodes reduces their numbers, whereas the numbers of intestinal stem cells are unaffected by nematode infection. Jonah66Ci knockdown further reduces nitric oxide levels in response to infection with symbiotic Steinernema nematodes. Finally, we show that Jonah66Ci knockdown does not alter the feeding rates of uninfected Drosophila larvae; however, infection with axenic Steinernema nematodes lowers larval feeding. In conclusion, we report that Jonah66Ci participates in maintaining homeostasis of certain physiological processes in Drosophila larvae in the context of Steinernema nematode infection. Similar findings will take us a step further toward understanding the molecular and physiological mechanisms that take place during parasitic nematode infection in insects.